2021
DOI: 10.7759/cureus.16119
|View full text |Cite
|
Sign up to set email alerts
|

ITSUS: Integrated, Tiered, Self-Directed Ultrasound Scanning for Learning Anatomy

Abstract: Ultrasound is being introduced into many medical schools and incorporated into the anatomy curriculum; however, in most cases, this consists of proctored sessions which can be limited by faculty time and availability. Additionally, the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic has significantly impacted medical education, especially ultrasound education, which has traditionally depended on hands-on practice and instruction. A structured, independent, hands-on learning curriculum usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Some of these approaches proved to be imperative for adapting US curricula for distance learning due to the Covid‐19 pandemic, as additional resources were required to provide hands‐on training to learners in different locations. While the pandemic forced most US curricula to be canceled, those that were adapted for virtual learning required extra faculty for lower in‐person faculty to student ratios and handheld US devices (Nix et al, 2021), additional tele‐US software and training (Soni et al, 2021), or didactic and US interpretation modules with lack of supervised hands‐on training (Boulger et al, 2021). Despite the additional resources, each of these studies found success in translating their US curricula, reinforcing the ability share approaches across institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these approaches proved to be imperative for adapting US curricula for distance learning due to the Covid‐19 pandemic, as additional resources were required to provide hands‐on training to learners in different locations. While the pandemic forced most US curricula to be canceled, those that were adapted for virtual learning required extra faculty for lower in‐person faculty to student ratios and handheld US devices (Nix et al, 2021), additional tele‐US software and training (Soni et al, 2021), or didactic and US interpretation modules with lack of supervised hands‐on training (Boulger et al, 2021). Despite the additional resources, each of these studies found success in translating their US curricula, reinforcing the ability share approaches across institutions.…”
Section: Discussionmentioning
confidence: 99%
“…In this example, local circumstances did not permit any hands‐on experience (Olivares‐Perez et al, 2022 ). As a second example, a series of self‐directed learning modules were developed for students who had requested ultrasound training in addition to that provided in their UME curriculum (Boulger et al, 2021 ). These modules with written so that students could work without the assistance of a faculty member by following detailed, step‐by‐step instructions using ultrasound instruments in the on‐campus laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…These modules with written so that students could work without the assistance of a faculty member by following detailed, step‐by‐step instructions using ultrasound instruments in the on‐campus laboratory. Students created a digital portfolio stored on the ultrasound machine that was periodically reviewed during an in‐person meeting with a faculty member (Boulger et al, 2021 ). A tele‐ultrasound course was developed for undergraduate medical students in response to discontinued in‐person teaching (Höhne et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some faculties reported positive experiences with self‐directed sonography curricula. For example, Boulger et al (2021) remodeled the on‐site content into an asynchronic format, where undergraduate students underwent the curriculum in a stepwise direction and prepared a portfolio with their own ultrasound images. Moreover, synchronous teleultrasound education with videoconferencing tools were shown to be feasible but inferior to the on‐site equivalent (Sexena et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, professional rituals, such as orientation events for first semester students, graduation or official events, such as white coat ceremonies were cancelled (Bidwell et al, 2016; Kinnear et al, 2021). As some institutes continued hands‐on training with strict hygienic restrictions, and a modified course format (Nourkami‐Tutdibi et al, 2021), synchronous videoconferencing the lectures or asynchronous e‐learning became a very popular alternative to compensate for a potential learning loss (Longhurst et al, 2020; Boulger et al, 2021; Sexena et al, 2021; Olivares‐Perez et al, 2022). In these cases, students maintained most of their learning experiences alone, at home, and in front of their computers.…”
Section: Introductionmentioning
confidence: 99%